Ekstraksi Ciri Pada Klasifikasi Tipe Kulit Wajah Menggunakan Metode Haar Wavelet - Muhammad Rafi Farhan; Agus Wahyu Widodo; Muhammad Arif Rahman (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Facial skin is one of the important parts of a human body. Lots of people trying to make their skin flawless. And also, most of them are willing to spend their money to achieve a perfect skin starts from treatment with distinguished doctors, applying expensive skin products or going abroad to get the product that matches with their skin type. The problem is, people are having difficulties on choosing the right product due to the nonconformity between the purchased product with the skin type. Moreover, this problem leads to acne, wrinkles, and black spot on the skin. The need for a system to ease non-expert to determine their skin type. So, they can purchase the product that fits their skin type. Therefore, the author propose to build a classification system which can classify skin types. In building that, the author uses haar wavelet method which is has been proven to get good result. Based on the result of this research, the highest accuracy is 90% in detection type of skin.